2019
DOI: 10.1097/mjt.0000000000000915
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Anticoagulation in Acute Coronary Syndrome

Abstract: Background: Both antiplatelets and anticoagulants are necessary in the management of acute coronary syndrome (ACS), although the exact proportion of antithrombotic effect that each drug and class should ideally provide remains a matter of ongoing study. Area of Uncertainty: Defining the best combination between the antiplatelet agents and oral anticoagulants (OACs) can be challenging. The choice is particularly important for special categories of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Moreover, the thrombotic risk did not increase by omitting aspirin, however, the trial was small and not powered for these events- [56]. This study reconfirms that warfarin as OAC worked better than the combination of aspirin plus clopidogrelin AF patients and showed that, despite a lesser frequency of bleeding events, there was similar ischaemic clinical benefit in a 6-week TAT versus a 6-month TAT [55,57].…”
Section: Warfarinmentioning
confidence: 68%
See 2 more Smart Citations
“…Moreover, the thrombotic risk did not increase by omitting aspirin, however, the trial was small and not powered for these events- [56]. This study reconfirms that warfarin as OAC worked better than the combination of aspirin plus clopidogrelin AF patients and showed that, despite a lesser frequency of bleeding events, there was similar ischaemic clinical benefit in a 6-week TAT versus a 6-month TAT [55,57].…”
Section: Warfarinmentioning
confidence: 68%
“…The primary safety end point for bleeding events was less frequent in both groups receiving rivaroxaban, as presented in Table 3. This trial adds new data on the use of low dose rivaroxaban in ACS patients and offersthe first clear signal for less bleeding with both reduced antithrombotic regimens-DAT (Rivaroxaban 15 mg/day and P2Y12 inhibitor), TAT with very low dose OAC (Rivaroxaban 2.5 mg twice daily) and DAPT [55,58]. PIONEER AF-PCI trial was not calibrated for ischaemic and thrombotic efficacy and low doses of rivaroxaban were not demonstrated to reduce stroke in AF patients [39,59].…”
Section: Rivaroxabanmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, finding effective and reliable neuroprotective agents for stroke treatment is urgent. Clopidogrel, a platelet aggregation inhibitor, was reported to work as a stroke preventative drug in vivo by slowing platelet aggregation [19]. The present study examined infarct size, cerebral edema, neurological behavior, and inflammatory cytokine levels of MCAO rats and OGD/R-induced SHSY5Y cells after BA intervention.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, finding effective and reliable neuroprotective agents for stroke treatment is urgent. Clopidogrel, a platelet aggregation inhibitor, was reported to work as a stroke preventative drug in vivo by slowing platelet aggregation [19].The…”
Section: Discussionmentioning
confidence: 99%